Living well with dementia groups: changes in participant and therapist verbal behaviour. (2nd January 2018) - Cheston, Richard; Marshall, Ann; Jones, Angharad; Spreadbury, John; Coleman, Peter
ABSTRACT: Objectives : This paper reports two related analyses of verbal material from seven Living Well with Dementia groups: the first examines changes in the verbal behaviours of participants across the course of the sessions in all seven groups; while the second contrasts therapist behaviour in two groups. Methods : In the first analysis, recordings of three sessions from each group were transcribed and participant descriptions of dementia were analysed using the Markers of Assimilation of Problematic Experiences of Dementia (MAPED) rating procedure. In the second analysis, therapist behaviour in weeks 2 and 8 from two groups (F and G) was analysed using the Hill Counsellor Verbal response rating scale. Inter-rater reliabilities for the two sets of ratings were 'good' and 'very good', respectively. Results : For the MAPED ratings, a five by four contingency table was analysed using chi-squared, which indicated a highly significant change in assimilation. There were significant higher levels of level 1 and 2 markers in the first two sessions and level 4 for sessions 5 and 6. Facilitators used significantly more direct guidance and information giving behaviour in the second session at Location F compared to Location G. Conclusions : The results suggest that important changes occurred in the way that dementia was described across the seven LivDem groups: this includes both reductions in the avoidance of direct references to dementia after the first two sessions, as well as an increase in 'insight' statements. Directive facilitator behaviour may be associated with poorer outcomes.